Person-centred care for dementia patients: back end system - Shi, Jiancheng (Nanyang Technological University, 2023)
Dementia, a group of cognitive impairments affecting memory and decision-making, is a pressing concern in Singapore, with nearly one in ten individuals aged 60 and above affected. The prevalence is expected to rise dramatically, needing customised care approach. Person-centered care prioritises individual needs, aiming to enhance dementia patient’s overall wellbeing and quality of life. As the number of patients increases, understanding and implementing person-Centred care become more crucial for effective support and management.